ChemInform Abstract: Novel Catalyst System for Hydrostannation of Alkynes. Issue 29 (22nd July 2014) - Gupta, Sreya; Do, Youngshil; Lee, Jin Hee; Lee, Miryeong; Han, Junghoon; Rhee, Young Ho; Park, Jaiwook
Abstract The catalyst can be recycled.